Menimbang Pentingnya Penguatan Kelembagaan Pemerintahan Desa - Hanantyo Sri Nugroho (Universitas Sultan Ageng Tirtayasa, 2018)
Abstract: The village is an autonomous region and existed before the state was formed. This is because the village has a self-governing community, where the right to manage and take care of himself. That is, the village has become a socio-political entity of its own. However, rural government institutions that have formed marginalized. The consequence is the loss of the village administration space to organize themselves. By using the character of qualitative research, this study tries to make sense of the importance of strengthening rural government institutions after the statute of the village. The results showed the openness of space owned by the village government prioritize economic development, while strengthening rural government institutions are still marginalized. Keywords: Institutional village administration; self-governing communityAbstrak: Desa merupakan wilayah yang otonom dan ada sebelum negara terbentuk. Hal ini dikarenakan desa memiliki self-governing community, dimana berhak mengatur maupun mengurus dirinya. Artinya, desa telah menjadi suatu entitas sosial-politik tersendiri. Namun, kelembagaan pemerintahan desa yang telah terbentuk mulai terpinggirkan. Konsekuensinya adalah hilangnya ruang pemerintahan desa untuk mengatur dirinya. Dengan menggunakan penelitian bersifat kualitatif, penelitian ini mencoba menalar pentingnya penguatan kelembagaan pemerintahan desa setelah adanya undang-undang desa. Hasil penelitian menunjukkan keterbukaan ruang yang dimiliki pemerintah desa mendahulukan pembangunan ekonomi, sedangkan penguatan kelembagaan pemerintahan desa masih terpinggirkan.Kata kunci: Kelembagaan pemerintahan desa; self-governing community